An integer programming approach to elective surgery scheduling in a Lisbon hospital - Marques, I.; M.E. Captivo; Pato, M.V. (Proceedings of the VII ALIO/EURO – Workshop on Applied Combinatorial Optimization, 2011)
Elective surgery planning is an important problem for any hospital. In particular, in Portugal, this problem reaches a level of great importance as it has direct relation with an ecient use of the operating theater, which also results on reducing waiting lists for surgery. Thus, a better surgical suite planning has economic and social impact. Both outcomes appear as guidelines of the Portuguese National Health Plan for 2004-2010. The authors present an integer linear programming model approach developed to address the elective surgery planning problem of a hospital in Lisbon, as well as results obtained with real data from the hospital. The results are analyzed in view of the impact on productivity indicators of the surgical suite and, as a consequence, on the hospital's waiting list for surgery.